Early national trends in non-abortion reproductive care access after Roe - Zhao, Junying; Zahn, Aaron; Pang, Samuel C.; Quang, Tony S.; Campbell, Janis; Halkitis, Perry N. (Frontiers in Public Health, 2024)
BACKGROUND No peer-reviewed evidence exists for spillover effects of overturning Roe on non-abortion reproductive care access. METHODS National data include 2013-2023 Title X Directory, 2013-2020 Artificial Reproductive Technologies (ART) Surveillance and 2021-2023 manual collection. We reported changes in ART clinics and Title X entities, and their associations with abortions. RESULTS Post-Roe America witnessed national declines of 1.03% in ART clinics and 18.34% in Title X entities. Reducing 100 abortions was associated with defunding two Title X entities. 83.39% of defunded Title X entities were in states that voted Republican in 2020 presidential election, disproportionate to the 49.02% of states that voted Republican and 42.52% of US population residing in these states. CONCLUSION Early evidence warns of worsening challenges of inequities and calls for policy actions.